Polymer scaffolds as drug delivery systems - Calori, Italo Rodrigo; Braga, Gustavo; de Jesus, Priscila da Costa Carvalho; Bi, Hong; Tedesco, Antonio Claudio (European polymer journal, 2020)
[Display omitted] •Polymer scaffolds (PS) as drug delivery systems (DDS) are reviewed.•Their fundamental points, polymer types, and common techniques are included.•Chemical modifications, triggers, and polymer blends can control the drug release.•PS are smart alternatives to traditional DDS to achieve the site-specific release. Drug delivery scaffolds are smart alternatives to conventional formulations and allow for controlled spatiotemporal releases of active compounds. In several fields of human health, various methods have emerged with natural and synthetic polymers that make the fabrication of new polymer scaffolds possible. This review provides an overview of all recently published studies on the development and application of polymer scaffolds targeting controlled drug delivery in medicinal fields, including regenerative medicine and cancer therapy. The review includes a summary of the most common types of polymers used in drug release scaffolds, polymer scaffold classes, and the most common fabrication methods employed to develop such scaffolds. A detailed overview is provided concerning the strategies used to load drugs into scaffolds and their effects on drug release. A discussion about the strategies applied to modulate drug delivery is introduced. This details polymer blends and responsive releases that target the control of the drug delivery rate. In addition, current examples of their applications are provided. These include anti-inflammatory drugs and growth factors, as well as more recent in vitro and in vivo assays. Finally, future perspectives of these biomedical devices in clinical applications are presented.